Design and Analysis of a Thyristor-Based Controlled Rectifier Circuit for Stabilization of Speed and Rotation in DC Motors - Jefry Setyo Fambudi; Rama Arya Sobhita (Journal of Marine Electrical and Electronic Technology, 2024)
Controlling the speed of a DC motor is relatively simpler compared to regulating the speed of other types of motors [1]. Various methods can be employed for DC motor speed control, including frequency adjustment, pole number variation, autotransformer modification, and regulation of the armature input voltage. Among these, the most commonly used technique involves controlling the input voltage supplied to the DC motor. This voltage control method leverages an optocoupler to handle low-voltage regulation and a Silicon Controlled Rectifier (SCR), also known as a Thyristor, to manage the input voltage via its gate terminal. The other terminals, "anode" and "cathode," function similarly to those of standard diodes. The SCR, a critical component in the Thyristor family, plays a pivotal role in regulating voltage in this application. In this study, a controlled rectifier circuit was designed and implemented for DC motor speed and rotation stabilization. The system comprises two primary subsystems: the control circuit and the power circuit. The control circuit employs an optocoupler to ensure precise power supply regulation and an SCR or Thyristor as the main controlling device. Meanwhile, the power circuit utilizes a 120 Volt AC input, which is subsequently converted to supply a DC motor. This research emphasizes the integration of these subsystems to achieve efficient and reliable speed stabilization, making it a significant contribution to the field of motor control systems and electrical engineering.